Differentiating Relationships in the Workplace: A Cultural Perspective - Halim, Haslina; Bakar, Hassan Abu; Mohamad, Bahtiar (International Review of Management and Marketing, 2016)
This study aimed to examine the constructs that constitute relationship differentiation in leader-member exchange relationships, which would provide unique theoretical insights and pragmatic applications for communication in the Malaysian workplace. Six-hundred questionnaires were distributed to employees of government, semi-government, and private organizations (N=479). Results revealed that leader conceptual skills, communication openness, and trust contributed towards organizational citizenship behavior. Cultural considerations were invoked to explain certain findings of this study. Keywords: Leader-Member Exchange (LMX), Communication Dialogue JEL Classification: M14